Earliness per se variation in Argentine bread wheat varieties and mapping of QTLs in a recombinant inbred line population - Lombardo, Lucio; Ghione, Celina Elena; Nisi, María Mercedes; Tranquilli, Gabriela; Helguera, Marcelo (Springer, 2019)
The occurrence of flowering time in wheat is affected not only by the vernalization and photoperiod response, but also by earliness per se (EPS). The effects of this trait facilitate the fine tunning of the life cycle for regional adaptation within mega environments. To contribute to the knowledge of the wheat germplasm grown in Argentina and to the understanding of the genetic basis underlying variation in EPS, this study aimed to characterize EPS in a set of modern local bread wheat varieties and to develop a biparental recombinant inbred line (RIL) population based on parental contrasting for EPS. The variation observed in flowering time, which was measured under satisfied vernalization and photoperiod demands and assignment of chromosomic regions by QTL analysis, constitutes the first genetic dissection of EPS control in Argentine wheat adapted materials, providing valuable information for regional adaptation in breeding programs. Based on EPS variation analysis, Baguette Premium 11 (late-heading variety) and BioINTA 2001 (early-heading variety) were selected to develop the mapping population. Six QTLs for EPS were detected in the biparental RIL population and QTL QEps.imj-5D1, in chromosome 5D, showed the greatest effect on EPS and is the first QTL to be reported in this chromosome.